Geographic Information Management in Local Government - Gilfoyle, Ian; Thorpe, Peter (CRC Press, 2004)
This volume examines the drivers that are necessary to ensure that real business benefits are delivered from the improved availability of geographic information. The Introduction covers the emergence of Geographic Information Management (GIM) and GIS in local government and explains why they are important. Part 2 explains the key elements of human and organizational issues, data, the technology toolbox, GIS selection and implementation, and coordinating mechanisms. Part 3 provides in-depth analyses of nine case studies of the use of technology by local UK authorities. Part 4 looks forward to the prospects and challenges for further GIM by local governments.